IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS PROGRAM SEKOLAHE AREK SUROBOYO (SAS) DALAM UPAYA PENCEGAHAN BULLYING DI SD HANG TUAH 7 SURABAYA - Wulandari, Rida; Fitria, Rezki Nurma; Karwanto, Karwanto; Nuphanudin, Nuphanudin; Amalia, Kaniati (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the implementation of character education based on the Sekolahe Arek Suroboyo (SAS) program in preventing bullying at SD Hang Tuah 7 Surabaya, including indicators of Safe, Recreational, Educational, and Mutual Cooperation, and analyze the factors that influence its success according to George C. Edward III's theory. This study uses a descriptive qualitative method with a case study design. Data were collected through interviews, observations, and documentation, and tested with triangulation of sources and techniques, then analyzed using the Miles, Huberman, and Saldana model. The results of the study indicate that character education based on the SAS program is implemented in accordance with the AREK indicators through scheduled habituation. The success of the program implementation is influenced by several factors, namely: (1) Internal and external communication is consistently established effectively through coordination, routine evaluation, and socialization; (2) resources are sufficient, although there are still constraints on the budget aspect so that infrastructure improvements are less than optimal; (3) the attitude of implementers shows a high commitment through support in learning, supervision, and habituation; (4) Bureaucratic structure, through a structured division of tasks and SOPs for activities, although there is no specific organizational structure.